Aproximación histórica del sector empresarial: Colombia y Boyacá. Siglos XIX y XX (2021)
This article aims to make a historical account in order to make an approximation to the business origin in global contexts, in Colombia and in Boyacá from the 19th and 20th centuries, with the aim of showing the genesis of this sector in a sense widespread. Although it has been approached from the research and included in the Business Administration programs of some universities in the country, this subject still deserves to be analyzed in greater depth in order to see that business legacy that has emerged over the years of the mentioned period, which has been highly significant for the economic development in Colombia and Boyacá. On the other hand, mention is made of the methodological aspects which correspond to the qualitative type of documentary exploratory nature, to account for some references used in the study and their results. The exhaustive bibliographic review became the technique used to address and analyze the problem. When examining the bibliographic references, it was found that in Boyacá only a few approaches have been made about the business context without mentioning the employer, leaving a Good part of this issue in the void.